2019
DOI: 10.3390/nano9010071
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interfacial Area between Dielectric Layer and Electrode of Triboelectric Nanogenerator toward Robustness and Boosted Energy Output

Abstract: Given the operation conditions wherein mechanical wear is inevitable, modifying bulk properties of the dielectric layer of a triboelectric nanogenerator (TENG) has been highlighted to boost its energy output. However, several concerns still remain in regards to the modification due to high-cost materials and cumbersome processes being required. Herein, we report TENG with a microstructured Al electrode (TENG_ME) as a new approach to modifying bulk properties of the dielectric layer. The microstructured Al elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In case of the back part, the output voltage with the capacitors of 0.1 and 0.3 µF was measured as 8.7 and 5.2 V respectively. The 0.3 µF capacitor charges slower than the 0.1 µF capacitor due to the higher loss of charges in the capacitor [80,83,84]. In addition, the output voltage of the front part with the 1, 3.3 and 10 µF capacitors were observed to be 0.78, 0.4 and 0.29 V respectively after charging the capacitors for 60s.…”
Section: Integration Of the Testec With Conventional Electronic Compomentioning
confidence: 98%
See 1 more Smart Citation
“…In case of the back part, the output voltage with the capacitors of 0.1 and 0.3 µF was measured as 8.7 and 5.2 V respectively. The 0.3 µF capacitor charges slower than the 0.1 µF capacitor due to the higher loss of charges in the capacitor [80,83,84]. In addition, the output voltage of the front part with the 1, 3.3 and 10 µF capacitors were observed to be 0.78, 0.4 and 0.29 V respectively after charging the capacitors for 60s.…”
Section: Integration Of the Testec With Conventional Electronic Compomentioning
confidence: 98%
“…Firstly, the output response of TESTEC was studied by integrating with a full wave bridge rectifier. Figure 5a After examining the device with the full bridge rectifier, the device was examined with capacitor to test the prospect of storing energy from the tapping and stepping motion as well as providing constant bias voltage to power touch based electronic equipment [80,83]. Figure 5d and 5e demonstrates schematic and optical view of the equivalent circuit diagram where the device was integrated with a full bridge rectifier and a capacitor.…”
Section: Integration Of the Testec With Conventional Electronic Compomentioning
confidence: 99%
“…Strategies so far used to improve TENGs power output include the search for novel, more efficient tribomaterials, [1,20,7] their nano and micro-structuration to increase the triboelectrification charging, [21] the use of charge trapping additives, [22][23][24] novel electrode engineering [25,26] and functional interlayers [27] placed at the interface between the electrode and the tribomaterial. Within this scenario, 2D materials have played a significant role [28][29][30] as they can be used as tribomaterials, [20] charge-trapping additives, [28] or electrodes as in the case of graphene-based electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of four modes of operation of triboelectric generators to generate electric potential, vertical contact mode where tribo materials are vertically moved apart; sliding mode where the tribo materials are slide apart, single electrode mode and free-standing mode the TENGs are used in various applications as energy recovery and regeneration system. Considering the mechanical wear of the materials in contact, vertical contact mode is of high significance in the research area for its improvement [9]. Studies have shown the efficiency of the TENG depends on the material aspects in terms of the morphology, geometry and properties.…”
Section: Introductionmentioning
confidence: 99%